2022
DOI: 10.31788/rjc.2022.1516588
|View full text |Cite
|
Sign up to set email alerts
|

COMPARATIVE STUDY OF Sida rhombifolia FROM TWO DIFFERENT LOCATIONS

Abstract: Sida rhombifolia or sidaguri, was taken from two regions in East Java Province, Indonesia, namely Batu (SB) and Ngawi (SN), was investigated in this study. The two samples were determined the content of secondary metabolites by using LC-MS/MS. They were also evaluated for their phytochemical content, total phenolic content (TPC), and antioxidants activity, using the DPPH and ABTS methods. The highest TPC (126.93 ± 0.63 mg GAE / g) was observed in the ethyl acetate fraction of SN. The antioxidant activity again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…33 The previous study concluded that the antioxidant activity may vary due to various factors such as the method of testing employed and the location from which the plant was collected. 34,35…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…33 The previous study concluded that the antioxidant activity may vary due to various factors such as the method of testing employed and the location from which the plant was collected. 34,35…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Eleven metabolites derived from phenolic acid and phenolic groups aldehydes were identified in the S. rhombifolia leaves, stems, and roots methanol extract. We successfully identified six phenolic acid metabolites, that is, caffeic acid (1), chlorogenic acid (2), ferulic acid (3), p-coumaric acid (4), salicylic acid (5), and vanillic acid (6), as well as four phenolic aldehyde compounds namely coniferaldehyde (7), ethoxyferulate (8), evofolin-A (9), sinapaldehyde (10), and syringaldehyde (11). The typical fragmentation pattern of phenolic acid metabolites releases the COOH, H2O, and RCOOH functional groups.…”
Section: Phenolicsmentioning
confidence: 99%
“…It is also known that secondary metabolites in plants are most commonly found on leaves because they are more easily affected by changes in environmental conditions [5] . For example, previous research has shown that sidaguri grown at different locations has different metabolite profiles [6] . Therefore, it is necessary to identify metabolites in S. rhombifolia leaves, stems, and roots at different cultivation ages as preliminary information about metabolite composition and concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation